2022
DOI: 10.7150/ijbs.78997
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in organotypic tissue slice cultures for anticancer drug development

Abstract: Organotypic tissue slice culture is established from animal or patient tissues and cultivated in an in vitro ecosystem. This technique has made countless contributions to anticancer drug development due to the vast number of advantages, such as the preservation of the cell repertoire and immune components, identification of invasive ability of tumors, toxicity determination of compounds, quick assessment of therapeutic efficacy, and high predictive performance of drug responses. Importantly, it serves as a rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 103 publications
(169 reference statements)
0
7
0
Order By: Relevance
“…We confirmed that the TSCs cultured for 24 hours maintained the cellular characteristics similar to the baseline state of the TME (i.e., T0 cell conditions at time of resection). As noted previously, other groups have used short culture periods to maintain the cellular diversity found in the native TME (47). First, we evaluated the TSC cellularity using hematoxylin and eosin ( H&E ) staining of the cultures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We confirmed that the TSCs cultured for 24 hours maintained the cellular characteristics similar to the baseline state of the TME (i.e., T0 cell conditions at time of resection). As noted previously, other groups have used short culture periods to maintain the cellular diversity found in the native TME (47). First, we evaluated the TSC cellularity using hematoxylin and eosin ( H&E ) staining of the cultures.…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 15, 2023. ; https://doi.org/10.1101/2023.03. 13.532299 doi: bioRxiv preprint tumor (4)(5)(6)(7). While TSCs have been used to evaluate the effects of chemotherapy agents in primary tumors specimens (8)(9)(10), only a limited number of recent studies have leveraged them to determine the consequences of immunotherapies such as anti-PD-1, anti-TIM-3, anti-IL-10 and CAR-T cells (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue slice culture prototype was first proposed by Dr. Harford's team and involved cutting the tissue into small pieces 42 . These tissue slices can be separated directly from normal organs and tumor tissues from humans and animals, providing the natural advantage of maintaining complex structural features and microenvironments in vitro 43 . However, tissue slices cannot be maintained under long‐term culture or expansion in vitro, with the culture period typically lasting 1 to 2 weeks only 44 .…”
Section: Tissue Slicing Technology and Tissue Slicesmentioning
confidence: 99%
“…While cell culture models can evaluate drugs quickly and inexpensively, they cannot fully replicate the in vivo environment. [ 4 ] Animal models can more accurately mimic the infection process, but they are time‐consuming and costly to conduct, making them more challenging. [ 5 ] Therefore, there is a need to develop rapid assessment methods that can accurately predict the efficacy of antiviral drugs in the brain and provide a reliable basis for their clinical translation.…”
Section: Introductionmentioning
confidence: 99%